2019
DOI: 10.1080/17469899.2019.1604222
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in glaucoma: old concepts, new ideas

Abstract: Introduction: The disease process of glaucoma is thought to begin up to twenty years before a diagnosis can be made. While its current treatment paradigm seeks to reduce the rate of disease progression through reducing intraocular pressure, these interventions are of limited effectiveness and are typically made late. Together, this highlights an unmet clinical need for development of novel techniques to facilitate the early diagnosis of glaucoma and the emergence of new treatment paradigms. This review provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…The authors also noticed that the use of high concentrations of curcumin inhibited not only apoptosis but also necrosis on TMCs [59]; which somehow contradicts another findings reviewed herein, such as the one stated by Park [52]. Furthermore, curcumin has proved to increase viability of RGC in other ocular diseases as described on the RIRI section of this review [53]. Curcumin has also been used to treat glaucoma in form of loaded nanoparticles [60], but this will be discussed later.…”
Section: Glaucomamentioning
confidence: 65%
See 1 more Smart Citation
“…The authors also noticed that the use of high concentrations of curcumin inhibited not only apoptosis but also necrosis on TMCs [59]; which somehow contradicts another findings reviewed herein, such as the one stated by Park [52]. Furthermore, curcumin has proved to increase viability of RGC in other ocular diseases as described on the RIRI section of this review [53]. Curcumin has also been used to treat glaucoma in form of loaded nanoparticles [60], but this will be discussed later.…”
Section: Glaucomamentioning
confidence: 65%
“…Glaucoma is one of the major causes of irreversible blindness, with over 60 million people affected worldwide and steadily growing [53,54]. It is a progressive optic neuropathy, characterized by the excavation of the optic nerve, due mainly to high ocular pressure, which leads to a progressive visual field loss by the loss of RGCs [55].…”
Section: Glaucomamentioning
confidence: 99%
“…To target these pathways, studies using models of glaucoma have shown promising results trialling neuroprotective therapies. Such agents include memantine that inhibits glutamate signalling, coenzyme Q10 as an anti‐oxidant and brimonidine which aside from its anti‐ocular hypertensive properties has long been proposed to possess neuroprotective effects 3 . Although clinical trials have shown promising initial results with coenzyme Q10 and brimonidine, large randomized controlled trials have failed to show efficacy 4 .…”
Section: Lowering Intraocular Pressure Cannot Be the Only Answermentioning
confidence: 99%
“…To complicate matters, trial‐related factors have been discussed as alternative explanations for these findings 5 . Recently, there has been renewed interest in compounds historically valued as medicinal, including curcumin found in turmeric and resveratrol contained in dark chocolate and red wine 3 . Both these compounds are thought to provide anti‐oxidant and anti‐inflammatory properties; however, their poor bioavailability has limited their use.…”
Section: Lowering Intraocular Pressure Cannot Be the Only Answermentioning
confidence: 99%
“…For these patients, nothing can be done to preserve vision because effective neuroprotective treatments do not exist. Furthermore, advances in the field are allowing for earlier diagnosis of glaucoma, at stages where neuroprotective intervention could have a greater impact on visual outcomes [4]. For these reasons, recent glaucoma research has focused on defining mechanisms of pathogenesis as well as developing and testing cell-based treatments that protect visual neurons.…”
Section: Introductionmentioning
confidence: 99%